Volume 5: Materials Technology; CFD and VIV 2008
DOI: 10.1115/omae2008-57599
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Carbon-Fiber Composite Repair System for Offshore Risers

Abstract: Composite systems are a generally-accepted method for repairing corroded and mechanically-damaged onshore pipelines. The pipeline industry has arrived at this point after more than 15 years of research and investigation. Because the primary method of loading for onshore pipelines is in the circumferential direction due to internal pressure, most composite systems have been designed and developed to provide hoop strength reinforcement. On the other hand, offshore pipes (especially risers), unlike onshore pipeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…They concluded that the use of composite overwrap could restore the bursting pressure resistance of both types of repaired pipes to the level of undamaged pipes. Alexander (2007) and Alexander and Ochoa (2010) performed experiments in conjunction with FEA and based on the obtained results presented an innovative design to extend the existing composite repair techniques to offshore pipes. Their research led to an easily deployable CFRP repair system based on the limit analysis method and strain-based design techniques.…”
Section: State Of the Artmentioning
confidence: 97%
See 1 more Smart Citation
“…They concluded that the use of composite overwrap could restore the bursting pressure resistance of both types of repaired pipes to the level of undamaged pipes. Alexander (2007) and Alexander and Ochoa (2010) performed experiments in conjunction with FEA and based on the obtained results presented an innovative design to extend the existing composite repair techniques to offshore pipes. Their research led to an easily deployable CFRP repair system based on the limit analysis method and strain-based design techniques.…”
Section: State Of the Artmentioning
confidence: 97%
“…A proper repair method should not only reinstate the original pressure capacity but also meet general criteria, such as ease of installation and economic viability, in addition to addressing technical criteria such as being impact resistance and nongalvanic (Alexander et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The technique used here, known as the double-elastic slope method was developed by Alexander [16] based on several industrial design codes and standards similar to Section 6-153 of ASME Boiler and Pressure Vessel Code, Section VIII, Division 2 [17]. The method required the load vs. strain response of uncorroded pipe to be simulated within an FE analysis and its gradient determined, i.e.…”
Section: Design Conditionsmentioning
confidence: 99%
“…It is expected that CFRTP will be applied not only to racing cars but also to commercial vehicles (Goto et al, 2011). When considering commercial applications, CFRTP may require more demands for repair during the product's life time (Alexander et al, 2008;Liu et al, 2012). However, there are only a few studies that focus on the repair properties of CFRTP under the actual damage such as bending damage.…”
Section: Introductionmentioning
confidence: 99%